PENGARUH PEMBERIAN EKSTRAK ETANOL 96% DAUN KELOR (Moringa oleifera L.) TERHADAP PEMERIKSAAN PROTHROMBIN TIME (PT) - Cinantya Kartika; Andri Sukeksi (Program Studi Teknologi Laboratorium Medik, 2021)
Prothrombin Time is important to examine the blood coagulation through extrinsic pathways and common pathways, namely FVII, FX, FV, prothrombin and fibrinogen. Prothrombin Time was measured manually with and without the addition of a 96 percent ethanol extract of Moringa leaves. The purpose of this study was to determine the effect of 96% ethanol extract of Moringa leaves on prothrombin time examination. 14 students from semester VI D-III Health Analysts at the University of Muhammadiyah Semarang were randomly selected for sampling. The results showed the average prothrombin time examination with 96% ethanol extract of Moringa leaves was 07.23 seconds, while the average prothrombin time examination without administration of 96% ethanol extract of Moringa leaves was 12.24 seconds. The results of the prothrombin time examination with the addiction of 96% ethanol extract of Moringa leaves were faster than without the provision of 96% ethanol extract of Moringa leaves. This study was found that there is a significant difference between the results of the prothrombin time examination with and without the addiction of 96% ethanol extract of Moringa leaves.